UWB/Wi-Fi RTT Integration for Personal Mobility Applications of CP User Groups - H. Perakis; G. Retscher; V. Gikas (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Modern mobile devices offer advanced capabilities for navigation and Location-Based Services (LBS). This study investigates the use of Ultra-Wideband (UWB) and Wi-Fi Round-Trip Time (RTT) measurements for pedestrian localization across various scenarios. We analyze the ranging accuracy of these techniques and evaluate positioning performance using different fusion algorithms. Our proposed collaborative positioning (CP) methodology enhances localization accuracy for user groups within a defined area. Results demonstrate significant improvements in position trueness, with UWB and Wi-Fi RTT achieving enhancements of 74% and 54%, respectively. Additionally, our localization algorithm, leveraging a Peer-to-Infrastructure (P2I) and Peer-to-Peer (P2P) hybrid configuration, increases anchor availability by up to 10%. Even in short-duration anchor loss scenarios (P2P-only), position trueness improves by up to 53%. These findings highlight the potential of UWB and Wi-Fi RTT in real-world pedestrian localization, particularly for urban navigation, smart mobility applications, and emergency response systems.